Definition of Seismic Input From Fault‐Based PSHA: Remarks After the 2016 Central Italy Earthquake Sequence. Issue 2 (15th February 2019) - Valentini, A.; Pace, B.; Boncio, P.; Visini, F.; Pagliaroli, A.; Pergalani, F.
Abstract: This work focuses on how the progress in earthquake science that follows a large, deeply studied earthquake might be promptly combined with updated approaches of seismic hazard analysis to guide applicative choices for seismic risk reduction, such as postevent seismic microzoning and building design. Both seismic microzoning and seismic design of structures require strong motion records to perform numerical site response analyses. These records have to be related to the seismotectonic context and historical seismicity of the investigation area. We first performed a fault‐based probabilistic seismic hazard analysis in the area struck by the 2016 central Italy seismic sequence to individuate reference uniform hazard spectra at rock conditions. We used two different seismic hazard models, one considering 27 individual seismogenic sources (ISSs), and the second one involving grid point seismicity, using a fixed‐radius smoothing approach. The geological and seismotectonic data of the 2016 seismic sequence were used to update the model of ISSs. We performed a deaggregation analysis to evaluate the contribution of the ISS in the hazard of four representative sites and to select the magnitude‐distance pairs useful in the selection of the real accelerograms. The deaggregation analysis has been performed to identify which source and magnitude most contribute to the hazard for each site, and for different periods of spectral accelerations. Finally, we select, for each site, a set of natural accelerograms, from both nonimpulsive and pulse‐like records, based on the magnitude‐distance pairs that are compatible on average with target uniform hazard spectra. Key Points: A fault‐based and time‐dependent approaches give a complementary view of PSHA We provide Input ground motion for site effects studies in central Italy We consider this approach useful for reconstruction projects